Assessment of the Remineralizing Efficacy of Grape Seed Extract vs Sodium Fluoride on Surface and Subsurface Enamel Lesions: An In Vitro Study - Deepak Sharma; Yogesh Sahu; Reema Srichand; Swapnali Mhatre; Uttam Shetty; Nikhil A. Karhale; Sonu Acharya (Journal of Pharmacy and Bioallied Sciences)
Background: Dental caries is a prevalent oral health issue, primarily resulting from demineralization of the enamel. Remineralizing agents such as sodium fluoride (NaF) have been widely used to counteract this process. Recent studies suggest that natural extracts, such as grape seed extract (GSE), may also have significant remineralizing properties. This study aims to compare the efficacy of GSE and NaF on surface and subsurface enamel lesions in an in vitro setting. Materials and Methods: In this in vitro study, 60 extracted human premolars were randomly divided into three groups of 20 each: control (no treatment), NaF treatment, and GSE treatment. Artificial enamel lesions were created on the buccal surfaces of all samples. The NaF group was treated with a 5% sodium fluoride solution, while the GSE group received a 6.5% grape seed extract solution. Treatments were applied daily for 10 days. Surface microhardness (SMH) and cross-sectional microhardness (CSMH) were measured before and after treatment to assess remineralization. Results: The NaF group showed a significant increase in SMH (45%) and CSMH (35%) compared to the control group. The GSE group demonstrated a similar trend with a 40% increase in SMH and a 30% increase in CSMH. Both treatments were significantly more effective than the control (P < 0.05), with no significant difference between the NaF and GSE groups (P > 0.05). Conclusion: Grape seed extract exhibits comparable remineralizing efficacy to sodium fluoride on both surface and subsurface enamel lesions in vitro. These findings suggest that GSE could be a viable natural alternative to fluoride for the prevention and treatment of dental caries.